2004
DOI: 10.1364/opex.12.001747
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Raman fiber laser temperature probe based on fiber Bragg gratings for long-distance remote sensing applications

Abstract: We demonstrate a practical and simple, all fiber Bragg grating (FBG) based Raman laser sensing probe for long-distance, remote temperature sensing application. Using multiple laser cavities based on FBG's and a tunable chirped FBG, we obtain the simultaneous multi-channel remote temperature sensing operation at a 50 km distance. The temperature sensitivity is measured to be 7.15 pm/ degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…However, the requirement of two separate light sources of a broadband light source and a Raman pump could be a limiting factor for practical implementation of such systems due to the corresponding higher system cost. Recently, P.-C. Peng et al proposed an advanced concept of the use of the linear cavity Raman laser configuration based on a FBG and fiber loop mirror for a long-distance strain sensing system [4] to obtain advantages such as high resolution and high optical signal-to-noise ratio (SNR) and our group also demonstrated a simple, all-FBG based long-distance Raman laser temperature sensing system [5]. Although the use of Raman laser configuration eliminates the requirement of an additional broadband light source and improves significantly the sensing signal quality, it would be very hard to achieve the simultaneous measurement of temperature and strain using the previous system configurations.…”
Section: Introductionmentioning
confidence: 92%
“…However, the requirement of two separate light sources of a broadband light source and a Raman pump could be a limiting factor for practical implementation of such systems due to the corresponding higher system cost. Recently, P.-C. Peng et al proposed an advanced concept of the use of the linear cavity Raman laser configuration based on a FBG and fiber loop mirror for a long-distance strain sensing system [4] to obtain advantages such as high resolution and high optical signal-to-noise ratio (SNR) and our group also demonstrated a simple, all-FBG based long-distance Raman laser temperature sensing system [5]. Although the use of Raman laser configuration eliminates the requirement of an additional broadband light source and improves significantly the sensing signal quality, it would be very hard to achieve the simultaneous measurement of temperature and strain using the previous system configurations.…”
Section: Introductionmentioning
confidence: 92%
“…A Micron Optics SM 125-500 optical interrogator has been used [21]. The most relevant features of this instrument are reported in Table II [22].…”
Section: Optoelectronic Read-out Systemmentioning
confidence: 99%
“…Murphy et al [8] have reported a silica fiber extrinsic Fabry-Pérot (FP) strain sensor to measure temperatures up to 975 • C. Alavie et al [9] have reported a serial multiplexed sensor system where each laser cavity was formed using an FBG and a broadband mirror, measuring the temperature from 20 • C to 160 • C. Kaddu et al [10] have reported multiplexed optical fiber FP sensor systems to measure temperature and strain over the ranges from 20 • C to 70 • C and from 0 to 400 µε, respectively. Peng et al [11] have reported an FBGbased temperature sensor system using a fiber laser to measure temperature over the range from 0 to 40 • C. A Raman fiber laser probe has also been developed [12] for long-distance remote temperature sensing applications, typically reported for use over the temperature range from 30 to 100 • C. Recently, fiber laser-based sensor systems have been developed to measure temperatures up to 500 • C in a single cavity configuration using a chirped FBG (CFBG) and a normal FBG in [13] and [14]. Additionally, some of the commercial manufacturing technologies are also available for temperature measurement applications [15], [16].…”
Section: A Parallel Multiplexed Temperature Sensor Systemmentioning
confidence: 99%